2021
DOI: 10.1002/app.50558
|View full text |Cite
|
Sign up to set email alerts
|

Simple approach for the plasma treatment of polymeric membranes and investigation of the aging effect

Abstract: The modification of the surface characteristics after treatment with plasma in polymeric materials, such as the aging phenomenon, calls the attention of research in the area of nonthermal plasma technology. In this work, a direct treatment with dielectric-barrier discharge plasma was used on the surfaces of ultrafiltration membranes. The measurements of the contact angle with water, attenuated total reflectance accessory, zeta potential, atomic force microscopy and scanning electron microscopy-MEV were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Plasma-treated membranes exhibited increased roughness and enhanced wettability, consistent with findings in the literature. 49,62,63 Kolsk a et al observed improved wettability and increased ness in a study involving argon plasma treatment on a PTFE surface under specific conditions. The present work's results are noteworthy as the improvements align with those reported in the literature using much simpler process parameters, justifying the use of such parameters.…”
Section: Membrane Surface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma-treated membranes exhibited increased roughness and enhanced wettability, consistent with findings in the literature. 49,62,63 Kolsk a et al observed improved wettability and increased ness in a study involving argon plasma treatment on a PTFE surface under specific conditions. The present work's results are noteworthy as the improvements align with those reported in the literature using much simpler process parameters, justifying the use of such parameters.…”
Section: Membrane Surface Characteristicsmentioning
confidence: 99%
“…For more comprehensive details, refer to a previously published article. 49 Membrane samples were sectioned and fixed in plastic Petri dishes to facilitate the surface (selective layer) modification process. The samples utilized in this study had a diameter of 8.5 cm.…”
Section: Modification Of the Membrane Surfacementioning
confidence: 99%
“…The gradual deterioration of the surface properties is the resultant of chain migration on the polymer surface 12–14,16,17,22,23 . The original hydrophobicity of the surface is retrograded due to diffusion of polar functional groups from the surface to the body, surface reaction, and reorientation of polar chemical group 12–14,16,24–29 . Innumerable experimental attempts like electric glow, plasma modification, and chemical vapor deposition have been contrived to improve the surface properties of polymer membranes 30 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14]16,17,22,23 The original hydrophobicity of the surface is retrograded due to diffusion of polar functional groups from the surface to the body, surface reaction, and reorientation of polar chemical group. [12][13][14]16,[24][25][26][27][28][29] Innumerable experimental attempts like electric glow, plasma modification, and chemical vapor deposition have been contrived to improve the surface properties of polymer membranes. 30 Surface modification of polymeric membranes by various plasma discharge has been performed by several researcher (Given in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…While plasma treatments are effective in improving polymer surface wettability, it is well established that these enhancements are not permanent [35,36]. A pronounced increase in wettability is typically observed immediately following plasma treatment, with a gradual decrease over time, to the point where the wettability of the surface almost matches the untreated polymer [10,37].…”
Section: Introductionmentioning
confidence: 99%